2007
DOI: 10.1007/s10152-007-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Terebellides kerguelensis stat. nov. (Polychaeta: Trichobranchidae) from Antarctic and subantarctic waters

Abstract: During the Spanish Antarctic expeditions " Bentart" 1994Bentart" , 1995Bentart" and 2003, a number of trichobranchid (Annelida: Polychaeta) specimens were collected and identiWed initially as Terebellides stroemii kerguelensis McIntosh, 1885, the only known species of the genus widely recognised as valid in Antarctic waters. In the framework of a worldwide revision of the genus Terebellides, a reconsideration of the taxonomic status of this subspecies of the boreal Terebellides stroemii Sars, 1835 is done t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Some of the recent molecular studies demonstrated the presence of bipolar species in some of the benthic invertebrate groups like amphipod crustaceans (Havermans et al, 2013), however, this result should be considered rather an exception from the rule (Brandt et al, 2012). There is a growing number of examples of polychaete species previously considered bipolar or cosmopolitan taxa turning out to be in fact species complexes (Scaps et al, 2000;Bleidorn et al, 2006;Barroso et al, 2010), and detailed taxonomic studies resulted in re-descriptions and changes in their taxonomic status (Parapar & Moreira, 2008). Nevertheless, Witman et al (2004) showed that the factors operating at different spatial scales can be responsible for the diversity patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recent molecular studies demonstrated the presence of bipolar species in some of the benthic invertebrate groups like amphipod crustaceans (Havermans et al, 2013), however, this result should be considered rather an exception from the rule (Brandt et al, 2012). There is a growing number of examples of polychaete species previously considered bipolar or cosmopolitan taxa turning out to be in fact species complexes (Scaps et al, 2000;Bleidorn et al, 2006;Barroso et al, 2010), and detailed taxonomic studies resulted in re-descriptions and changes in their taxonomic status (Parapar & Moreira, 2008). Nevertheless, Witman et al (2004) showed that the factors operating at different spatial scales can be responsible for the diversity patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other polychaete taxa thought as having a wide distribution and previously reported from the Southern Ocean might actually not be represented there. This is the case of the northern trichobranchid Terebellides stroemii Sars, 1835 which was supposed to be represented at southern latitudes by the subspecies T. stroemii kerguelensis McIntosh, 1885, which recently Parapar and Moreira (2008), after revision of the type material, proposed elevated to the species rank leaving the distribution of T. stroemiilimited to northern latitudes.…”
Section: General Remarksmentioning
confidence: 99%
“…Both cruises were carried out onboard the R/V Hespérides during the austral summers of 2002-2003 and 2005-2006 respectively. Some results on polychaetes have been published by Parapar and Moreira (2008), López (2008López ( , 2010López ( , 2011, Parapar et al (2011), and Moreira and Parapar (2011).…”
Section: Introductionmentioning
confidence: 86%